Comparative study of 1D de-noising techniques using induction motor fault signals - Lamia, Rehnuma Tasnim; Iqbal, Zafor (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.